2014
DOI: 10.1097/pas.0000000000000109
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features of Adult T-cell Leukemias/Lymphomas at a North American Tertiary Care Medical Center

Abstract: Human T-cell lymphotropic virus type 1 is associated with adult T-cell leukemia/lymphoma (ATLL). Published series of ATLLs seen at a United States medical institution are rare. We present the features of 4 ATLLs diagnosed at our North American tertiary care medical center from 1990 to 2012. Despite the absence of a history of origin from an endemic region, all our ATLLs demonstrated evidence of human T-cell lymphotropic virus type 1 infection. Central nervous system (CNS) involvement by ATLL was uncommon in ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Although cerebral T-cell lymphomas are frequently reported ( 8 , 13 ), there are no reports on T-LPD in the CNS. This case was clinically characterized by EBV+ T-cell proliferation in the CNS, with an indolent period and developed a progressive course soon.…”
Section: Discussionmentioning
confidence: 99%
“…Although cerebral T-cell lymphomas are frequently reported ( 8 , 13 ), there are no reports on T-LPD in the CNS. This case was clinically characterized by EBV+ T-cell proliferation in the CNS, with an indolent period and developed a progressive course soon.…”
Section: Discussionmentioning
confidence: 99%
“…Hsi et al [21] found 64 cases of primary or secondary CNS lymphomas at their institution in a 13-year retrospective analysis. Only 12.5% (8 cases) represented T-cell lymphomas (1 case of adult T-cell leukemia/lymphoma, 1 of monomorphic posttransplant lymphoproliferative disorder of T-cell type and 6 of T-cell lymphoblastic leukemia/lymphoma).…”
Section: Discussionmentioning
confidence: 99%
“…Some T-cell lymphoma entities, like adult T-cell leukemia-lymphoma (ATLL), peripheral T-cell lymphomas-no other specified (PTCL-NOS), ALK-positive ALCL (ALK + ALCL), and ENKTCL seem to be associated with an increased risk of CNS dissemination (Table 1), an event rarely reported in patients with angioimmunoblastic T-cell lymphoma Gurion et al, 2016;Ellin et al, 2015;Kim et al, 2020;Pro and Perini, 2010). CNS involvement occurs in 10-25% of patients with ATLL (Rubenstein et al, 2008;Gurion et al, 2016;Yi et al, 2011;Kim et al, 2010;Teshima et al, 1990), but it is very rare initial diagnosis (Ma et al, 2014); higher risk of CNS relapse is reported in the forms with disseminated disease, such as lymphomatous and acute forms, especially the former, which represents almost half the ATLL patients (Kitajima et al, 2002;Hsi et al, 2014). However, the rate of CNS dissemination in ATLL patients may be underestimated; this is suggested by a study showing that 14 % of ATLL patients without neurological symptoms had evidence of CNS involvement on autopsy (Teshima et al, 1990).…”
Section: Incidence Of Cns Dissemination By T-cell Lymphoma Entitymentioning
confidence: 99%
“…However, the rate of CNS dissemination in ATLL patients may be underestimated; this is suggested by a study showing that 14 % of ATLL patients without neurological symptoms had evidence of CNS involvement on autopsy (Teshima et al, 1990). In addition, CNS relapse seems to be more common in ATLL patients with leukocytosis, hypercalcemia, or elevated serum lactate dehydrogenase (LDH) levels (Hsi et al, 2014). In ENKTCL, nasal type, CNS dissemination was strongly related to the natural killer prognostic index (NKPI includes B symptoms, stage III or IV, elevated serum LDH concentration, and lymph node involvement), with a CNS relapse rate of 1.8 % for patients with NKPI score 1-2 and 10.2 % for patients with NKPI 3-4 (Kim et al, 2010).…”
Section: Incidence Of Cns Dissemination By T-cell Lymphoma Entitymentioning
confidence: 99%